Case Report: Gigantic Arteriovenous Femoral Fistula Following Cardiac Artery Catheterization - Russu, Eliza; Mureşan, Adrian Vasile; Kaller, Reka; Coşarcă, Cătălin Mircea; Arbănaşi, Eliza-Mihaela; Arbănaşi, Emil-Marian (Frontiers in Surgery, 2022)
Purpose: To present the case of a patient with a 9-mm iatrogenic fistula between a branch of the right profunda femoris artery, aneurysmally dilated at approximately 1.851cm, and the right femoral vein, successfully treated with open surgical ligation. Case report: A 70-years-old female was referred to the Vascular Surgery Clinic due to worsening car-diac failure symptoms during the previous year. The medical history included a diagnostic cardiac artery catheterism through a Seldinger technique one year and a half ago. A recent ultrasound described veloc-ities characteristic for a high flow arteriovenous communication in the right groin. Two consecutive cardiology exams, performed at nine months from one another, showed a decrease of almost 21% in the ejection fraction of the left ventricle. An angiography was conducted with the hope of achieving effec-tive percutaneous embolization. Unfortunately, that was not the case. An open repair was scheduled, as the option for a stent-graft deployment was overruled as being too risky, potentially closing several branches of the profunda femoris artery and not fully completing the orifice due to a complicated ana-tomical positioning. Under local anesthesia, an open ligation was performed in very hostile anatomical conditions. The patient had an uncomplicated evolution and was discharged on the third day, symptom-free. Conclusions: Iatrogenic arteriovenous fistulas are rare. Clinical presentation diagnoses the case effi-ciently, vascular imaging being essential for surgical preparation. Though open repair is not the gold standard, there are cases not suitable for the endovascular approach. These patients are eligible for a surgical solution, not without technical challenges.